Confocal Endomicroscopy of Colorectal Polyps. (26th January 2012) - Ussui, Vivian M.; Wallace, Michael B.
Abstract : Confocal laser endomicroscopy (CLE) is one of several novel methods that provide real-time, high-resolution imaging at a micron scale via endoscopes. CLE has the potential to be a disruptive technology in that it can change the current algorithms that depend on biopsy to perform surveillance of high-risk conditions. Furthermore, it allows on-table decision making that has the potential to guide therapy in real time and reduce the need for repeated procedures. CLE and related technologies are often termed "virtual biopsy" as they simulate the images seen in traditional histology. However, the imaging of living tissue allows more than just pragmatic convenience; it also allows imaging of living tissue such as active capillary circulation, cellular death, and vascular and endothelial translocation, thus extending beyond what is capable in traditional biopsy. Immediate potential applications of CLE are to guide biopsy sampling in Barrett's esophagus and inflammatory bowel disease surveillance, evaluation of colorectal polyps, and intraductal imaging of the pancreas and bile duct. Data on these applications is rapidly emerging, and more is needed to clearly demonstrate the optimal applications of CLE. In this paper, we will focus on the role of CLE as applied to colorectal polyps detected during colonoscopy.